Economic Evaluation of Nonpharmacological Interventions for Dementia Patients and their Caregivers - A Systematic Literature Review - Sanjib Saha; Ulf-G. Gerdtham; Håkan Toresson; Lennart Minthon; Johan Jarl (Lund University, School of Economics and Management, Department of Economics, 2018)
Background: The rising prevalence of dementia represents an important public health issue. There is currently no available cure for dementia disorders, only symptom-relieving therapies which can be either pharmacological or non-pharmacological. The number of non-pharmacological interventions for patients with dementia disorders and their caregivers have been increasing in recent years without much knowledge on their cost-effectiveness. The objective is to review the existing evidence on cost-effectiveness of non-pharmacological interventions targeting patients with dementia disorders, their caregivers, and the patient-caregiver dyad. Method: A systematic search of published economic evaluation studies in English was conducted using specified key words in relevant databased and websites. Data extracted included methods and empirical evidence (costs, effects, ICER) and we assessed if the conclusions made in terms of cost-effectiveness were supported by the reported evidence. The included studies were also assessed for reporting quality using the Consolidated Health Economic Evaluation Reporting Standards (CHEERS) checklist. Results: We included seventeen studies in this review categorised into three groups: physical exercise, occupational therapy, and psychological/psychosocial treatment. In almost all the studies (except one), economic evaluation was performed for a randomised controlled trial alongside the non-pharmacological intervention or retrospectively. There was a considerable heterogeneity in methodological approaches, target populations, study time frames, and perspectives as well as types of intervention. This prevents an informative comparison between most of the studies. However, we found that physical exercise was the most-effective non-pharmacological interventions for patients with dementia. For occupational therapy and psychological/psychosocial interventions we found mixed results although the majority was not cost-effective. Conclusion: More economic evaluations studies are required in non-pharmacological interventions. However, the interventions need to have a strong study design with the intention to perform economic evaluation in parallel.
Keywords: H43; I10; I18; 330; Dementia; Non-pharmacological interventions; Caregivers